Rancang Bangun Sistem Enkripsi dan Dekripsi SMS Menggunakan AES dan Blowfish Cipher serta Kombinasinya Pada Telepon Seluler Berbasis Android - Putra, I Putu Warma; Sudarma, Made; Pramaita, Nyoman (Majalah Ilmiah Teknologi Elektro; Vol 18 No 1 (2019): (Januari - April) Majalah Ilmiah Teknologi Elektro, 2019)
One of the facilities provided by cellular phones is to send data in the form of short messages via Short Message Service (SMS). Most people use SMS services more often than phone services because they are cheap and easy to use. Open networks, easy access, standard platform and open source development bring security threats such as viruses, phishing, spam on SMS. Security information in SMS can be done by encrypting messages to be sent. The AES (Advanced Encryption Standard) algorithm is a standard for data encryption, suitable for scenarios where memory and processing capabilities are very limited as in mobile devices. Encryption for text data types can also use the Blowfish algorithm, where the Blowfish algorithm can perform encryption and decryption with better performance compared to other symmetric algorithms if packet data size changes. Research designing systems that can be utilized by users who want to send a confidential information to someone via SMS without fear of information from the message will be known by others. The method used by the system in encrypt and decrypt the message is AES method and Blowfish Cipher which implementation using java programming language on Android.